Dynamic postural control two years following anterior cruciate ligament reconstruction in a female collegiate soccer player - Samaan, M. A.; Greska, E. K.; Hoch, M. C.; Weinhandl, J. T.; Bawab, S. Y.; Ringleb, S. I. (International Journal of Athletic Therapy & Training, 2015)
Context: ACL injury may cause a lack of knee joint proprioception and motor control due to knee joint instability. ACL reconstruction restores knee joint stability, yet dynamic postural control may still be affected while performing dynamic tasks.